An Assessment of Geotechnical Characteristics of Gharraf Oil Field Area Using Electrical Resistivity Test - Shaia Hussein A. (Civil and Environmental Engineering)
Geotechnical characteristics of soil are very important for civil applications and engineers because the structures almost construct and built on the ground such as high buildings, towers, bridges, tunnels and others on the soils. Electrical resistivity (ER) measurements are nowadays widely used to evaluate the geotechnical characterization of soil as they are fast, time-consuming and costly and non-destructive. This article provides the data of soil electrical resistivity measurements carried out on different zones and sites in Gharraf oil field area (northwestern part of the Thi-Qar governorate in the south east of Iraq). In this study the analyses of the obtained data were carried out to propose a new empirical quantitative correlation between soil resistivity and geotechnical characteristics. The improved empirical relationships reflect a very good correlation and it were found that the electrical resistivity of soil has a significant assessment and good fitting with the some of important geotechnical parameters. It was also concluded that the electrical resistivity method which has an advantage over other soil investigation methods that saving and reduce cost. Finally, the new generated empirical equation can be used to evaluate the ultimate bearing capacity of the soil rather than using the traditional widely used equations which require several inputs coefficients calculated using the extensive laboratory and field works. However, the results showed a good and more reliable correlation between soil electrical resistivity and some geotechnical characteristics for the studied region soil.